2018
DOI: 10.33202/comuagri.503629
|View full text |Cite
|
Sign up to set email alerts
|

Hidrojel-Perlit Karışımlarının Salata (Lactuca sativa var.crispa ) Yetiştiriciliğinde Verim ve Bazı Kalite Parametreleri Üzerine Etkilerinin Belirlenmesi

Abstract: Hidrojel-perlit karışımlarının topraksız tarımda marul yetiştiriciliğinde verim ve bazı kalite parametreleri  üzerine etkilerinin belirlenmesi üzerine ele alınan çalışma, 2017 yılında Çanakkale Onsekiz Mart Üniversitesi Bahçe Bitkileri Bölümü’ne ait soğuk serada yürütülmüştür. Deneme; tesadüf blokları deneme desenine göre 3 tekerrürlü olarak oluşturulmuştur. Hidrojel-perlit denemesi yetiştirme ortamları: 1) 16 litre perlit + 0 g hidrojel (kontrol), 2) 14 litre perli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Roots grown in HP treated soils showed the weakest development in a loam soil. Some researchers reported that hydrogel application reduced root and shoot growth of plants (Keever et al, 1989) and negatively affected plant growth (İşlek and Öztokat Kuzucu, 2018). In this research amended clay loam soil by OPC, P and HP enhanced plant root growth.…”
Section: Effects Of Different Soil Conditioners On Plant Root Parametersmentioning
confidence: 61%
“…Roots grown in HP treated soils showed the weakest development in a loam soil. Some researchers reported that hydrogel application reduced root and shoot growth of plants (Keever et al, 1989) and negatively affected plant growth (İşlek and Öztokat Kuzucu, 2018). In this research amended clay loam soil by OPC, P and HP enhanced plant root growth.…”
Section: Effects Of Different Soil Conditioners On Plant Root Parametersmentioning
confidence: 61%